X-Git-Url: http://lambda.jimpryor.net/git/gitweb.cgi?p=lambda.git;a=blobdiff_plain;f=advanced_topics%2Fmonads_in_category_theory.mdwn;h=173160e51c310018c87b43984820f3ffcffd176e;hp=402a5e778d16520463b1d149ffe54661d55ea02c;hb=446376aee15c6fbc9d71383d1c7654fd02ebb8f6;hpb=9905c7069d7b4d2f8b9ffbeccaa12d6c64382a8a diff --git a/advanced_topics/monads_in_category_theory.mdwn b/advanced_topics/monads_in_category_theory.mdwn index 402a5e77..173160e5 100644 --- a/advanced_topics/monads_in_category_theory.mdwn +++ b/advanced_topics/monads_in_category_theory.mdwn @@ -1,6 +1,3 @@ -**Don't try to read this yet!!! Many substantial edits are still in process. -Will be ready soon.** - Caveats ------- I really don't know much category theory. Just enough to put this @@ -8,11 +5,16 @@ together. Also, this really is "put together." I haven't yet found an authoritative source (that's accessible to a category theory beginner like myself) that discusses the correspondence between the category-theoretic and functional programming uses of these notions in enough detail to be sure that -none of the pieces here is misguided. In particular, it wasn't completely -obvious how to map the polymorphism on the programming theory side into the -category theory. And I'm bothered by the fact that our `<=<` operation is only -partly defined on our domain of natural transformations. But this does seem to -me to be the reasonable way to put the pieces together. We very much welcome +none of the pieces here is mistaken. +In particular, it wasn't completely obvious how to map the polymorphism on the +programming theory side into the category theory. The way I accomplished this +may be more complex than it needs to be. +Also I'm bothered by the fact that our `<=<` operation is only partly defined +on our domain of natural transformations. +There are three additional points below that I wonder whether may be too +cavalier. +But all considered, this does seem to +me to be a reasonable way to put the pieces together. We very much welcome feedback from anyone who understands these issues better, and will make corrections. @@ -51,12 +53,12 @@ To have a category, the elements and morphisms have to satisfy some constraints: (ii) composition of morphisms has to be associative - (iii) every element E of the category has to have an identity - morphism 1E, which is such that for every morphism f:C1→C2: + (iii) every element X of the category has to have an identity + morphism 1X, which is such that for every morphism f:C1→C2: 1C2 ∘ f = f = f ∘ 1C1 -These parallel the constraints for monoids. Note that there can be multiple distinct morphisms between an element `E` and itself; they need not all be identity morphisms. Indeed from (iii) it follows that each element can have only a single identity morphism. +These parallel the constraints for monoids. Note that there can be multiple distinct morphisms between an element `X` and itself; they need not all be identity morphisms. Indeed from (iii) it follows that each element can have only a single identity morphism. A good intuitive picture of a category is as a generalized directed graph, where the category elements are the graph's nodes, and there can be multiple directed edges between a given pair of nodes, and nodes can also have multiple directed edges to themselves. Morphisms correspond to directed paths of length ≥ 0 in the graph. @@ -65,14 +67,14 @@ Some examples of categories are: * Categories whose elements are sets and whose morphisms are functions between those sets. Here the source and target of a function are its domain and range, so distinct functions sharing a domain and range (e.g., `sin` and `cos`) are distinct morphisms between the same source and target elements. The identity morphism for any element/set is just the identity function for that set. -* any monoid (S,⋆,z) generates a category with a single element `x`; this `x` need not have any relation to `S`. The members of `S` play the role of *morphisms* of this category, rather than its elements. All of these morphisms are understood to map `x` to itself. The result of composing the morphism consisting of `s1` with the morphism `s2` is the morphism `s3`, where s3=s1⋆s2. The identity morphism for the (single) category element `x` is the monoid's identity `z`. +* any monoid (S,⋆,z) generates a category with a single element `Q`; this `Q` need not have any relation to `S`. The members of `S` play the role of *morphisms* of this category, rather than its elements. All of these morphisms are understood to map `Q` to itself. The result of composing the morphism consisting of `s1` with the morphism `s2` is the morphism `s3`, where s3=s1⋆s2. The identity morphism for the (single) category element `Q` is the monoid's identity `z`. -* a **preorder** is a structure (S, ≤) consisting of a reflexive, transitive, binary relation on a set `S`. It need not be connected (that is, there may be members `s1`,`s2` of `S` such that neither s1≤s2 nor s2≤s1). It need not be anti-symmetric (that is, there may be members `s1`,`s2` of `S` such that s1≤s2 and s2≤s1 but `s1` and `s2` are not identical). Some examples: +* a **preorder** is a structure (S, ≤) consisting of a reflexive, transitive, binary relation on a set `S`. It need not be connected (that is, there may be members `s1`,`s2` of `S` such that neither s1 ≤ s2 nor s2 ≤ s1). It need not be anti-symmetric (that is, there may be members `s1`,`s2` of `S` such that s1 ≤ s2 and s2 ≤ s1 but `s1` and `s2` are not identical). Some examples: * sentences ordered by logical implication ("p and p" implies and is implied by "p", but these sentences are not identical; so this illustrates a pre-order without anti-symmetry) * sets ordered by size (this illustrates it too) - Any pre-order (S,≤) generates a category whose elements are the members of `S` and which has only a single morphism between any two elements `s1` and `s2`, iff s1≤s2. + Any pre-order (S,≤) generates a category whose elements are the members of `S` and which has only a single morphism between any two elements `s1` and `s2`, iff s1 ≤ s2. Functors @@ -229,12 +231,12 @@ If φ is a natural transformation from `F` to `M(1C)` and
 	γ = (φ G')
 	  = ((unit <=< φ) G')
+	  since unit is a natural transformation to M(1C), this is:
 	  = (((join 1C) -v- (M unit) -v- φ) G')
 	  = (((join 1C) G') -v- ((M unit) G') -v- (φ G'))
 	  = ((join (1C G')) -v- (M (unit G')) -v- γ)
 	  = ((join G') -v- (M (unit G')) -v- γ)
-	  since (unit G') is a natural transformation to MG',
-	  this satisfies the definition for <=<:
+	  since (unit G') is a natural transformation to MG', this is:
 	  = (unit G') <=< γ
 
@@ -245,11 +247,11 @@ Similarly, if ρ is a natural transformation from `1C` to `MR'`,
 	γ = (ρ G)
 	  = ((ρ <=< unit) G)
+	  = since ρ is a natural transformation to MR', this is:
 	  = (((join R') -v- (M ρ) -v- unit) G)
 	  = (((join R') G) -v- ((M ρ) G) -v- (unit G))
 	  = ((join (R'G)) -v- (M (ρ G)) -v- (unit G))
-	  since γ = (ρ G) is a natural transformation to MR'G,
-	  this satisfies the definition <=<:
+	  since γ = (ρ G) is a natural transformation to MR'G, this is:
 	  = γ <=< (unit G)
 
@@ -265,10 +267,10 @@ Summarizing then, the monad laws can be expressed as: (ii) (ρ <=< γ) <=< φ = ρ <=< (γ <=< φ) (iii.1) (unit G') <=< γ = γ - when γ is a natural transformation from some FG' to MG' + whenever γ is a natural transformation from some FG' to MG' (iii.2) γ = γ <=< (unit G) - when γ is a natural transformation from G to some MR'G + whenever γ is a natural transformation from G to some MR'G @@ -282,7 +284,7 @@ In category theory, the monad laws are usually stated in terms of `unit` and `jo P3. functors "preserve identity", that is for every element C1 in F's source category: F(1C1) = 1F(C1). --> -Let's remind ourselves of some principles: +Let's remind ourselves of principles stated above: * composition of morphisms, functors, and natural compositions is associative @@ -290,9 +292,9 @@ Let's remind ourselves of some principles: * if η is a natural transformation from `G` to `H`, then for every f:C1→C2 in `G` and `H`'s source category C: η[C2] ∘ G(f) = H(f) ∘ η[C1]. -* (η F)[E] = η[F(E)] +* (η F)[X] = η[F(X)] -* (K η)[E} = K(η[E]) +* (K η)[X] = K(η[X]) * ((φ -v- η) F) = ((φ F) -v- (η F)) @@ -388,126 +390,221 @@ Finally, we substitute ((join G') -v- (M γ) -v- φ) for (i') ((join G') (M γ) φ) etc are also in T + - - +
 	    (ii) (ρ <=< γ) <=< φ  =  ρ <=< (γ <=< φ)
 	==>
-		    (ρ <=< γ) is a transformation from G to MR', so
-			(ρ <=< γ) <=< φ becomes: ((join R') (M (ρ <=< γ)) φ)
+		     (ρ <=< γ) is a transformation from G to MR', so
+			 (ρ <=< γ) <=< φ becomes: ((join R') (M (ρ <=< γ)) φ)
 							which is: ((join R') (M ((join R') (M ρ) γ)) φ)
 
-			similarly, ρ <=< (γ <=< φ) is:
+			 similarly, ρ <=< (γ <=< φ) is:
 							((join R') (M ρ) ((join G') (M γ) φ))
 
-		 	substituting these into (ii), and helping ourselves to associativity on the rhs, we get:
-	        ((join R') (M ((join R') (M ρ) γ)) φ) = ((join R') (M ρ) (join G') (M γ) φ)
+		 	 substituting these into (ii), and helping ourselves to associativity on the rhs, we get:
+	         ((join R') (M ((join R') (M ρ) γ)) φ) = ((join R') (M ρ) (join G') (M γ) φ)
     
-			which by the distributivity of functors over composition, and helping ourselves to associativity on the lhs, yields:
-	       ((join R') (M join R') (MM ρ) (M γ) φ) = ((join R') (M ρ) (join G') (M γ) φ)
+			 which by the distributivity of functors over composition, and helping ourselves to associativity on the lhs, yields:
+	         ((join R') (M join R') (MM ρ) (M γ) φ) = ((join R') (M ρ) (join G') (M γ) φ)
   
-			which by lemma 1, with ρ a transformation from G' to MR', yields:
-	       ((join R') (M join R') (MM ρ) (M γ) φ) = ((join R') (join MR') (MM ρ) (M γ) φ)
-
-			which will be true for all ρ,γ,φ just in case:
-	        ((join R') (M join R')) = ((join R') (join MR')), for any R'.
+			 which by lemma 1, with ρ a transformation from G' to MR', yields:
+	         ((join R') (M join R') (MM ρ) (M γ) φ) = ((join R') (join MR') (MM ρ) (M γ) φ)
 
-			which will in turn be true just in case:
-
-      (ii') (join (M join)) = (join (join M))
+			 [-- Are the next two steps too cavalier? --]
 
+			 which will be true for all ρ, γ, φ only when:
+	         ((join R') (M join R')) = ((join R') (join MR')), for any R'
 
+			 which will in turn be true when:
+       (ii') (join (M join)) = (join (join M))
+
+
 	 (iii.1) (unit G') <=< γ  =  γ
 	         when γ is a natural transformation from some FG' to MG'
-	(iii.1) (unit F') <=< φ  =  φ
 	==>
-			(unit F') is a transformation from F' to MF', so:
-				(unit F') <=< φ becomes: (join F') (M unit F') φ
-						   which is: (join F') (M unit F') φ
-				substituting in (iii.1), we get:
-			((join F') (M unit F') φ) = φ
-
-			which will be true for all φ just in case:
+			 (unit G') is a transformation from G' to MG', so:
+			 (unit G') <=< γ becomes: ((join G') (M (unit G')) γ)
+			                      which is: ((join G') ((M unit) G') γ)
 
-	         ((join F') (M unit F')) = the identity transformation, for any F'
+			 substituting in (iii.1), we get:
+			 ((join G') ((M unit) G') γ) = γ
 
-			which will in turn be true just in case:
-
-	(iii.1') (join (M unit) = the identity transformation
+			 which is:
+			 (((join (M unit)) G') γ) = γ
 
+			 [-- Are the next two steps too cavalier? --]
 
+			 which will be true for all γ just in case:
+			 for any G', ((join (M unit)) G') = the identity transformation
 
+			 which will in turn be true just in case:
+	(iii.1') (join (M unit)) = the identity transformation
+
- (iii.2) γ = γ <=< (unit G) +
+	 (iii.2) γ  =  γ <=< (unit G)
 	         when γ is a natural transformation from G to some MR'G
-	(iii.2) φ  =  φ <=< (unit F)
 	==>
-			φ is a transformation from F to MF', so:
-				unit <=< φ becomes: (join F') (M φ) unit
-				substituting in (iii.2), we get:
-			φ = ((join F') (M φ) (unit F))
-						   --------------
-				which by lemma (2), yields:
-                            ------------
-			φ = ((join F') ((unit MF') φ)
+			 γ <=< (unit G) becomes: ((join R'G) (M γ) (unit G))
+			
+			 substituting in (iii.2), we get:
+			 γ = ((join R'G) (M γ) (unit G))
+		
+			 which by lemma 2, yields:
+			 γ = (((join R'G) ((unit MR'G) γ)
 
-				which will be true for all φ just in case:
+			 which is:
+			 γ = (((join (unit M)) R'G) γ)
 
-	        ((join F') (unit MF')) = the identity transformation, for any F'
+			 [-- Are the next two steps too cavalier? --]
 
-				which will in turn be true just in case:
+			  which will be true for all γ just in case:
+			 for any R'G, ((join (unit M)) R'G) = the identity transformation
 
+			 which will in turn be true just in case:
 	(iii.2') (join (unit M)) = the identity transformation
 
Collecting the results, our monad laws turn out in this format to be: - - when φ a transformation from F to MF', γ a transformation from F' to MG', ρ a transformation from G' to MR' all in T: +
+	For all ρ, γ, φ in T,
+	where φ is a transformation from F to MF',
+	γ is a transformation from G to MG',
+	ρ is a transformation from R to MR',
+	and F'=G and G'=R:
 
-	(i') ((join G') (M γ) φ) etc also in T
+	    (i') ((join G') (M γ) φ) etc also in T
 
-	(ii') (join (M join)) = (join (join M))
+	   (ii') (join (M join)) = (join (join M))
 
 	(iii.1') (join (M unit)) = the identity transformation
 
-	(iii.2')(join (unit M)) = the identity transformation
+	(iii.2') (join (unit M)) = the identity transformation
 
Getting to the functional programming presentation of the monad laws -------------------------------------------------------------------- -In functional programming, unit is usually called "return" and the monad laws are usually stated in terms of return and an operation called "bind" which is interdefinable with <=< or with join. - -Additionally, whereas in category-theory one works "monomorphically", in functional programming one usually works with "polymorphic" functions. +In functional programming, `unit` is sometimes called `return` and the monad laws are usually stated in terms of `unit`/`return` and an operation called `bind` which is interdefinable with `<=<` or with `join`. The base category C will have types as elements, and monadic functions as its morphisms. The source and target of a morphism will be the types of its argument and its result. (As always, there can be multiple distinct morphisms from the same source to the same target.) -A monad M will consist of a mapping from types C1 to types M(C1), and a mapping from functions f:C1→C2 to functions M(f):M(C1)→M(C2). This is also known as "fmap f" or "liftM f" for M, and is called "function f lifted into the monad M." For example, where M is the list monad, M maps every type X into the type "list of Xs", and maps every function f:x→y into the function that maps [x1,x2...] to [y1,y2,...]. +A monad `M` will consist of a mapping from types `'t` to types `M('t)`, and a mapping from functions f:C1→C2 to functions M(f):M(C1)→M(C2). This is also known as liftM f for `M`, and is pronounced "function f lifted into the monad M." For example, where `M` is the list monad, `M` maps every type `'t` into the type `'t list`, and maps every function f:x→y into the function that maps `[x1,x2...]` to `[y1,y2,...]`. + +In functional programming, instead of working with natural transformations we work with "monadic values" and polymorphic functions "into the monad." +A "monadic value" is any member of a type `M('t)`, for any type `'t`. For example, any `int list` is a monadic value for the list monad. We can think of these monadic values as the result of applying some function `phi`, whose type is `F('t)->M(F'('t))`. `'t` here is any collection of free type variables, and `F('t)` and `F'('t)` are types parameterized on `'t`. An example, with `M` being the list monad, `'t` being `('t1,'t2)`, `F('t1,'t2)` being `char * 't1 * 't2`, and `F'('t1,'t2)` being `int * 't1 * 't2`: +
+	let phi = fun ((_:char, x y) -> [(1,x,y),(2,x,y)]
+
+ + + +Now where `gamma` is another function of type F'('t) → M(G'('t)), we define: + +
+	gamma =<< phi a  =def. ((join G') -v- (M gamma)) (phi a)
+	                 = ((join G') -v- (M gamma) -v- phi) a
+					 = (gamma <=< phi) a
+
-A natural transformation t assigns to each type C1 in C a morphism t[C1]: C1→M(C1) such that, for every f:C1→C2: - t[C2] ∘ f = M(f) ∘ t[C1] +Hence: + +
+	gamma <=< phi = fun a -> (gamma =<< phi a)
+
+ +`gamma =<< phi a` is called the operation of "binding" the function gamma to the monadic value `phi a`, and is usually written as `phi a >>= gamma`. + +With these definitions, our monadic laws become: + + +
+	Where phi is a polymorphic function of type F('t) -> M(F'('t))
+	gamma is a polymorphic function of type G('t) -> M(G'('t))
+	rho is a polymorphic function of type R('t) -> M(R'('t))
+	and F' = G and G' = R, 
+	and a ranges over values of type F('t),
+	b ranges over values of type G('t),
+	and c ranges over values of type G'('t):
+
+	      (i) γ <=< φ is defined,
+			  and is a natural transformation from F to MG'
+	==>
+		(i'') fun a -> gamma =<< phi a is defined,
+			  and is a function from type F('t) -> M(G'('t))
+
+ +
+	     (ii) (ρ <=< γ) <=< φ  =  ρ <=< (γ <=< φ)
+	==>
+			  (fun a -> (rho <=< gamma) =<< phi a)  =  (fun a -> rho =<< (gamma <=< phi) a)
+			  (fun a -> (fun b -> rho =<< gamma b) =<< phi a)  =  (fun a -> rho =<< (gamma =<< phi a))
+
+	   (ii'') (fun b -> rho =<< gamma b) =<< phi a  =  rho =<< (gamma =<< phi a)
+
+ +
+	  (iii.1) (unit G') <=< γ  =  γ
+	          when γ is a natural transformation from some FG' to MG'
+	==>
+			  (unit G') <=< gamma  =  gamma
+			  when gamma is a function of type F(G'('t)) -> M(G'('t))
+
+			  fun b -> (unit G') =<< gamma b  =  gamma
+
+			  (unit G') =<< gamma b  =  gamma b
+
+			  Let return be a polymorphic function mapping arguments of any
+			  type 't to M('t). In particular, it maps arguments c of type
+			  G'('t) to the monadic value (unit G') c, of type M(G'('t)).
+
+	(iii.1'') return =<< gamma b  =  gamma b
+
+ +
+	  (iii.2) γ  =  γ <=< (unit G)
+	          when γ is a natural transformation from G to some MR'G
+	==>
+			  gamma  =  gamma <=< (unit G)
+			  when gamma is a function of type G('t) -> M(R'(G('t)))
+
+			  gamma  =  fun b -> gamma =<< (unit G) b
+
+			  As above, return will map arguments b of type G('t) to the
+			  monadic value (unit G) b, of type M(G('t)).
+
+			  gamma  =  fun b -> gamma =<< return b
+
+	(iii.2'') gamma b  =  gamma =<< return b
+
-The composite morphisms said here to be identical are morphisms from the type C1 to the type M(C2). +Summarizing (ii''), (iii.1''), (iii.2''), these are the monadic laws as usually stated in the functional programming literature: +* `fun b -> rho =<< gamma b) =<< phi a = rho =<< (gamma =<< phi a)` + Usually written reversed, and with a monadic variable `u` standing in + for `phi a`: -In functional programming, instead of working with natural transformations we work with "monadic values" and polymorphic functions "into the monad" in question. + `u >>= (fun b -> gamma b >>= rho) = (u >>= gamma) >>= rho` -For an example of the latter, let φ be a function that takes arguments of some (schematic, polymorphic) type C1 and yields results of some (schematic, polymorphic) type M(C2). An example with M being the list monad, and C2 being the tuple type schema int * C1: +* `return =<< gamma b = gamma b` - let φ = fun c → [(1,c), (2,c)] + Usually written reversed, and with `u` standing in for `gamma b`: -φ is polymorphic: when you apply it to the int 0 you get a result of type "list of int * int": [(1,0), (2,0)]. When you apply it to the char 'e' you get a result of type "list of int * char": [(1,'e'), (2,'e')]. + `u >>= return = u` -However, to keep things simple, we'll work instead with functions whose type is settled. So instead of the polymorphic φ, we'll work with (φ : C1 → M(int * C1)). This only accepts arguments of type C1. For generality, I'll talk of functions with the type (φ : C1 → M(C1')), where we assume that C1' is a function of C1. +* `gamma b = gamma =<< return b` -A "monadic value" is any member of a type M(C1), for any type C1. For example, a list is a monadic value for the list monad. We can think of these monadic values as the result of applying some function (φ : C1 → M(C1')) to an argument of type C1. + Usually written reversed: + `return b >>= gamma = gamma b` +